Development of an assessment tool for motor praxis ability in children aged 5-8 years - Korrawan Ruttanathantong (2018)
Objectives: To develop a Motor Praxis Ability Test (MPAT) and examine its psychometric properties. Methods: The study consisted of two phases: items and scoring criteria of MPAT were developed in phase I. Content validity was clarified by the expert panel discussion method. The preliminary psychometric properties of the MPAT were examined in phase II. Data were collected with two samples consisting of typically-developing children and dyspraxic children. Results: The results revealed high internal consistency reliability. The inter-rater and test-retest reliability for the total score of both sample groups were excellent. The results also revealed that the MPAT was able to discriminate between typical children and dyspraxic children. Conclusion: The current study concluded that the MPAT is a highly valid and reliable assessment tool. It can be also used as an appropriate assessment tool for screening and evaluating dyspraxia in children aged 5-8 years. © 2013 Informa UK Ltd.